Reconstruction after bipalpebral resection with preservation of the eyeball: aesthetic and functional challenge - Henri Friedhofer; Rodolfo Costa Lobato; Aneta Hionia Vassiliadis; Maira Benito Scapolan; Mateus Neves da Silva de Jesus; Juan Felippe Guimarães Urcioli Mosquera de Rodriguez; José Yoshikazu Tariki; Rolf Gemperli (Revista Brasileira de Cirurgia Plástica, 2021)
Introduction: Eyelid reconstruction can be performed by primary closure, a graft of different lamellae, and local and/or regional flaps, single or combined. This reconstruction becomes more complex when the upper and lower eyelids are resected to total thickness, and the eyeball is preserved. The objective is to report the techniques used for periorbital reconstruction in bipalpebral resection cases (upper and lower) with preservation of the eyeball by the Group of Orthopalpebral Surgery of the Division of Plastic Surgery and Burns of HCFMUSP. Methods: All cases that met the inclusion criteria from 2000 to 2019 were reviewed, and epidemiological, surgical, and postoperative follow-up data were described. Results: Only two cases were submitted to total exeresis of the periorbital tissue and remained susceptible to eyeball preservation. Both were reconstructed with frontal flaps with complete occlusion of the eyeball at the first moment, followed by the release in stages, keeping the globe viable after reconstruction completion. Discussion: Similar reports are scarce in the literature, and, in these cases, surgical results were functionally acceptable but with significant aesthetic limitations. Conclusion: We suggest a new option for total reconstruction of the upper and lower eyelid (with a single pedicular flap, devoid of connective graft and in multiple stages) that protects and conserves the eyeball during the various stages of surgery. The results were functionally favorable, considering the severity of the cases.